Tracing the Use of Cognitive Strategies by Non-English Students in Learning English - Talok, Damianus; Hornay, Priscilla Maria Assis; Djehatu, Maria Goreti (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
The objectives of the current research are to identify and quantify the cognitive strategies non-English students use when working on assignments or solving problems of the English language they are learning and seek to find out non-English students’ motivation and background knowledge of English as sustaining factors related to the use of numerous cognitive strategies leading to the success of learning. This research employed a case study qualitative approach. Data were taken from observations and interviews and were analyzed using thematic analysis. Results of this research show that non-English students treated as the subject of this research employed the so-called cognitive strategies in doing all tasks, including auditory representation, repetition, note-taking, resourcing, inferring, translation, and transfer. Although most students had only the so-called instrumental motivation, weak interest, and also, they lacked knowledge of English, yet it is proven that the cognitive strategies they employed have enabled them to do all given tasks. An important implication of this study is that learning should include training and supporting the students to understand the importance of learning strategy.